A rare case of recurrent HHV6 encephalitis in an immunocompetent adult - Al-Asmar, Rania (IDCases, 2021)
Human Herpesvirus 6 (HHV-6) is a virus known to cause mild infection in children. In adults, HHV-6 reactivation has been described in immunocompromised individuals.Rarely, viral reactivation occurs in immunocompetent adults causing significant disease and morbidity. The use of certain medications, like amoxicillin, has been found to induce HHV-6 reaction in a number of cases. We report a 63-year-old immunocompetent female who presented with headache, fever and altered mental status. Past medical history included two bouts of HHV-6 encephalitis treated at external facilities. According to her medical history, both episodes of encephalitis were preceded by amoxicillin use. Her lumbar puncture analysis was consistent with viral etiology and a cerebrospinal fluid (CSF) PCR was positive for HHV-6. She was successfully treated with intravenous ganciclovir. It is important to keep a broad differential diagnosis in mind when approaching encephalitis in adults, and to be aware of unusual triggers for viral reactivation. Clinicians who suspect the infection in the correct clinical setting can successfully treat patients with recurrent HHV-6.